Thermodynamic and economic analyses and multi-objective optimization of harvesting waste heat from a biomass gasifier integrated system by thermoelectric generator. (1st September 2019) - Khanmohammadi, Shoaib; Saadat-Targhi, Morteza; Al-Rashed, Abdullah A.A.A.; Afrand, Masoud
Highlights: Possibility of integrating thermoelectric with gasifier cycle is investigated. Different locations for adding TEG in a biomass power generation is investigated. Adding thermoelectric to the condenser section increases efficiency from 16.76% to 17.93%. Economic evaluation indicated the conditions under which the system is profitable. Abstract: Thermoelectric waste heat recovery systems (WHRSs) can be used appropriately to recover wasted heat from various industrial processes. In the current work, new thermodynamic modeling was developed to harvesting waste heat from an integrated system includes an externally fired gas turbine and a biomass gasifier by three thermoelectric WHRSs. The biomass system consisted a gas turbine cycle, an organic Rankine cycle (ORC) and a domestic water heater were first thermodynamically modeled, and then effects of adding thermoelectric WHRSs to different locations of the system were investigated. It is observed that first law efficiency of the system ( η 1 ) will become 17.11% (an increase of 0.35%) if the total output heat from the stack enters W H R S s . The efficiencies of the system can be increased from 16.76% to 17.93% by placing a WHRS on the condenser of ORC. Moreover, the operating parameters have a significant effect on the integrated system efficiency; the influence of increasing α G E on the efficiencies is in contrast to the effect of enhancing α c o n d . In addition, an economic assessment of integrating WHRSs with the biomass gasifier integrated system is conducted and the conditions are indicated under which the proposed system is profitable. Furthermore, the results of genetic algorithm based multi-objective optimization shows that with the use of γ DU  = 2 and γ L, O R C = 30 defined thermal efficiencies are at their optimum state.